Target Channel Selection Algorithm for Cognitive Radio Network - K.S, Yuvaraj; P., Priya; V., Thiagarasu (International Journal of Engineering and Technology, 2018)
Cognitive radio network has attained more popularity because of giving prominent solution for spectrum inefficiency due to static spectrum allocation. This research proposed target channel selection algorithm which have been employed to improving the throughput and reducing number of handoffs. The proposed target channel selection algorithm is select the channel based on the idle probability and efficiency reward of channel and these are calculated from the surveillance of earlier usage statistics. When the channel selection is based on the above factor, the Secondary User gets chance to utilize the Primary user channel in maximum time to achieve optimal goal. The results show that proposed algorithm-based channel selection shows the better performance than existing algorithms in factors such as throughput, number of handoffs and collision rate.Â